EFFECT OF SELF-HYPNOSIS THERAPY AND MASSAGE COUNTER PRESSURE ON THE INTENSITY OF DYSMENORHEA PAIN IN WOMEN ADOLESCENT - muchlishatun ummiyati ummi; Elok Sari Dewi (Universitas STRADA Indonesia, 2023)
Background of study: The incidence of dysmenorrhea in Indonesia is 64.2%, Non-pharmacological therapies that are safer, more comfortable and economical include self hypnosis and massage counter pressure techniques. Methods: This study was a quantitative study with a quasi-experimental design. The samples in this study were young women aged 13-18 years in Kepuh Village, Kertosono. measuring the dysmenorrhea pain scale using the Numerical Rating Scale (NRS) Results: Bit showed a decrease in the average Dysmenorhoe pain intensity score in women adolescent in Kepuh village, Kertosono District. Analysis: The results of statistical tests using the paired sample T test show that the Sig.(2-tailed) value is 0.000 < α (0.05). Then H0 is rejected. it means that there is a significant difference in the average reduction in pain intensity. Conclusion: Giving Self Hypnosis and Massage Counter Pressure treatment can reduce the intensity of Dysmenorhea pain in young women.